Comparison of Depression, Anxiety and Stress with Quality of Life among Pregnant Women - Aysha Butt, Sidra Javid, Nauman Mazhar, Saqib Bajwa, Sumaira Afzal, Rabbia Ashraf, Umair Muddasar (Pakistan Journal of Medical & Health Sciences, 2022)
The study aimed to find the correlation and prediction of depression, anxiety, stress and quality of life in pregnant women in a local setup. Co-relational research design and purposive sampling were used. Data included 106 pregnant women with an average age of 31 years. Co relational analysis revealed that depression, anxiety and stress were significantly negatively related to the quality of life. Moreover, regression analysis found that depression inversely predicted quality of life. Study has significant implications for couple counseling and marital therapy in order to increase the psychological health of females and to protect newborn babies and pregnant mothers from the effects of psychological distress. Keywords: depression stress, anxiety, quality of life, pregnant women